An Empirical Investigation on the Relationship Between the Eurozone ZEW Index and the Eurozone Stock Markets - Ceylan, Nesrin; Münyas, Turgay (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
The aim of this study is to investigate the long and short term impact of the Euro ZEW index (ZEW) on the DAX (GDAXI) Germany, FTSE 100 (FTSE) the UK, CAC 40 (FCHI) France, OMXS30 Sweden and CROBEX (CRBEX) Croatia stock market indices using monthly data for the period between February 2008 and December 2020. The Euro ZEW Index was taken as the independent variable, and the index values of Eurozone stock markets were taken as the dependent variables. As a result of the study, the Euro ZEW index was found to have a positive (increasing) statistical significant effect on the DAX, FTSE, OMXS and CRBEX variables. Of the stock markets studied, Croatia CROBEX (CRBEX) index was the most affected index by the change in the Euro ZEW index. The least affected stock market was Germany DAX (GDAXI) index. The effect of the Euro ZEW Index on Euro stock markets was higher in the short-term, and gradually decreasing in the long term. The research findings are discussed in the conclusion section.